DON’T WAIT TO FIND ORANG-UTANS ONLY IN BOOKS - EXPERT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 17 December 2015 " Let us avoid from being blamed by future generations if the orangutan could only be found solely in books and visual recordings then."